PROTOCOL: Interventions promoting resilience through climate-smart agricultural practices for women farmers: A systematic review - Saran, Ashrita; Singh, Sabina; Gupta, Neha; Walke, Sujata Chodankar; Rao, Ranjana; Simiyu, Christine; Malhotra, Suchi; Mishra, Avni; Puskur, Ranjitha; Masset, Edoardo; White, Howard; Waddington, Hugh Sharma (Wiley, 2022)
This is the protocol for a Campbell systematic review. The objectives are as follows: the primary objective of this review is to synthesise evidence of the effectiveness of interventions to promote climate‐smart agriculture to enhance agricultural outcomes and resilience of women farmers in low‐and‐middle‐income countries (research question 1). The secondary objective is to examine evidence along the causal pathway from access to interventions to promote climate‐smart agriculture to empowering women so that they can use climate‐smart technology. And such outcomes include knowledge sharing, agency improvement, resource access and decision‐making (research question 2).